5PSQ-058 Efficacy and marginal cost of treatment with tocilizumab in COVID-19 patients. (23rd March 2022) - Garcia, A; Alos, M; Sanchez, R; Anton, M; Ferriols, R
Abstract : Background and importance: Pharmacological treatment of SARS-CoV-2 infection focuses primarily on antiviral and immunomodulatory agents. Tocilizumab is a humanised monoclonal antibody that binds to the IL-6 receptor (IL6-R) that has been used to combat the disease. Effectiveness results in controlled trials are controversial and therefore it is necessary to evaluate the evolution of patients in real clinical practice, as well as the cost of treatment. Aim and objectives: The aim of this study was to evaluate overall survival of patients treated with tocilizumab and the factors that influence survival. In addition, the marginal cost of treatment with tocilizumab is analysed. Material and methods: Retrospective observational study in a cohort of COVID-19 patients (n=508) treated with tocilizumab. The time period of the selected patients was 1 year. Patients were stratified according to hospitalisation unit (intensive care unit (ICU) or non-ICU) at the time of administration of the first dose of tocilizumab. Survival was assessed by Cox regression. The costs assumed were the acquisition costs and were evaluated using the cost-effectiveness ratio. Costs were analysed by bootstrapping in each subgroup. The efficacy measure was calculated as the restricted median survival (RMST). The cost-effectiveness ratio was calculated as the ratio cost (€)/RMST (years). SPSS software was used for analysis. Results: Age and ICU hospitalisation negatively affect the survival of patients treated with tocilizumab. Patients older than 71.5 years have a worse survival rate than younger patients (58.8% vs 88.7%, p=0.000). Survival rate of ICU patients vs non-ICU patients was 67.7% vs 79.1% (p=0.037). The mean cost of treatment in our cohort was €534.07/year (€697.84/year in patients older than 71.5 years vs €466.82/year in younger patients). Conclusion and relevance: Treatment with tocilizumab in patients with COVID-19 is more effective in patients admitted to the non-ICU versus ICU. In addition, survival is higher in younger patients aged 71.5 years. The mean cost of treatment with tocilizumab was €534.07/year. The cost-effectiveness ratio is important from the healthcare payer's point of view because it is indicative of the cost of treatment per unit of efficacy measured in survival years in each subgroup. There is a bias in treatment efficacy due to the different severity of ICU and non-ICU patients. References and/or acknowledgements: Conflict of interest: No conflict of interest